2019
DOI: 10.3390/su11113140
|View full text |Cite
|
Sign up to set email alerts
|

Macro Asset Allocation with Social Impact Investments

Abstract: Using a unique dataset of 50 listed companies that meet the majority of the OECD requirements for social impact investments, we construct a social impact finance stock index and investigate how investing in social impact firms can contribute to portfolio risk-return performance. We build portfolios with three different methodologies (naïve, Markowitz mean-variance optimization, GARCH-copula model), and we study the performance in terms of returns, Sharpe ratio, utility, and forecast premium based on a constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 37 publications
(51 reference statements)
0
22
0
3
Order By: Relevance
“…In the case of ROE and in addition to all of the previous finance variables, Biasin et al (2019) indicate that there is a positive relationship between the implementation of sustainable practices and all company finance variables, such as ROA, ROE, earnings per share, market value, share value, and EBITDA. ROE was found to be positively correlated with the index in 39% of the companies that are part of the DJSI and in 43% of the companies that are part of the general IGPA.…”
Section: Discussionmentioning
confidence: 90%
“…In the case of ROE and in addition to all of the previous finance variables, Biasin et al (2019) indicate that there is a positive relationship between the implementation of sustainable practices and all company finance variables, such as ROA, ROE, earnings per share, market value, share value, and EBITDA. ROE was found to be positively correlated with the index in 39% of the companies that are part of the DJSI and in 43% of the companies that are part of the general IGPA.…”
Section: Discussionmentioning
confidence: 90%
“…Anyway, other positive results associated with responsible financial products were found even without considering financial crisis periods. For example, Biasin et al [32]-one of the last studies before the pandemic-highlight the benefits of social impact investmentbased portfolios. Abate et al [33], using a sample of European funds, and Das et al [34] showed that socially responsible mutual funds outperformed conventional funds and Ouchen [35] demonstrated that the ESG portfolio MSCI USA ESG Select was "less turbulent".…”
Section: Related Literaturementioning
confidence: 99%
“…Ning and Sobel (2018) deal with the connection between the market volatility and dividend rates, maintaining that growing endogenous values of capacities and cash coincide with the increased insecurity of the development, to which companies respond by reducing payout ratios. Biasin et al (2019) point out an apparent paradox phenomenon of increasing the value in companies including the earning payout in the form of investments in programmes of corporate social responsibility in terms of reviewing the company performance discussing yields on model portfolios in the sample of 50 enterprises listed on stock markets. Hsu (2018) analyses the same area, claiming that CSR (Corporate Social Responsibility) presents a functional predictor for determining the company life-cycle and, apart from other, earning management.…”
Section: Literature Reviewmentioning
confidence: 99%